Can Statins Improve Outcomes After Isolated Cardiac Valve Surgery? A Systematic Literature Review. Issue 8 (13th May 2013) - Chacko, Jacob; Harling, Leanne; Ashrafian, Hutan; Athanasiou, Thanos
Abstract Background HMG CoA (3‐hydroxy‐3‐methylglutaryl coenzyme A) reductase inhibitors, or statins, have been associated with an improvement in outcomes after coronary artery surgery for some time; however, their role in isolated valve surgery (IVS) remains undetermined. Hypothesis The pleiotropic effects of statins may produce similar beneficial effects on outcomes after IVS. Methods A systematic review of the literature was performed investigating the role of statins in bioprosthetic valve replacement. Results Nine observational studies (7 retrospective, 2 prospective) incorporating a total of 18 154 patients were found investigating the role of statin therapy in bioprosthetic valve replacement. Conclusions There is presently insufficient evidence to recommend routine statin therapy in IVS, unless concomitant hypercholesterolemia or coronary artery disease is present. A prospective study clearly defining the dose, type, and duration of therapy is now required to finally clarify whether statins alone confer a postoperative benefit in these patients.